Tujuan Penerapan Manajemen SDM di PT Jarum - Gusnila Putriza; Hendra Riofita (STIKes Ibnu Sina Ajibarang, 2024)
Human resources (HR) in the company need to be managed professionally in order to create a balance between employee needs and the demands and capabilities of the company's organization. This balance is the main key for the company to be able to develop productively and fairly. HR always plays an active and dominant role in every organizational activity, because humans become planners, actors and determinants of the realization of organizational goals. Human resource management has a major role in every institutional activity. Although supported by facilities and infrastructure and excessive funding sources, without the support of reliable human resources, institutional activities will not run well, this shows that human resources are the main key that must be considered with all its needs. The method used is a literature review, which is a scientific study that focuses on a particular topic. Literature review will provide an overview of the development of a particular topic. Literature review will allow a researcher to identify a theory or method, develop a theory or method, identify gaps that occur between a theory and relevance in the field / to a research result. The results of the study stated that Human Resource Management (HR) is one of the most vital aspects in the success of an organization or company. At PT Jarum, the implementation of HR management aims to create synergy between employees, management, and the company's strategic goals. This goal does not only include achieving short-term results such as productivity, but also includes long-term efforts to ensure the company's desires and the welfare of its employees.